Study on Control Strategy for Composite Power Supply System of EV. Issue 5 (January 2021) - Tian, Liyuan; Liu, Xiaofei
Abstract: At present, countries all over the world are vigorously developing new energy vehicles. Many countries and regions have introduced policies to stop the production and sales of traditional energy vehicles. However, the large-scale industrialization of pure electric vehicles has encountered the constraints of power batteries, and its main problems are reflected in the specific power of the power battery is low. This paper analyzes the current situation of electric vehicle composite power supply, points out the problems and solutions of electric vehicle energy storage system, in order to obtain the expected development and test results.